Analysis of the Suitability of Fortigate Firewall Performance Limiting the Use of Social Media Streaming During Operating Hours at PT. Asaba Digital Innotech - Saputra, Erwan; Budi Santoso, Gatot; Sediyono, Agung (Penerbitan Universitas Trisakti, 2025)
Initial network analysis at PT ASABA Digital Innotech identified very high bandwidth consumption for non-work activities, with total usage in 30 days reaching 195 GB for social media and 448 GB for streaming media. This research aims to implement and measure the effectiveness of access restriction policies using Fortigate firewalls to significantly reduce this traffic. Using the Network Development Life Cycle (NDLC) method, a rule policy based on FortiGuard Web Filtering and Application Control was designed to block access during working hours (08.00-17.00), with the exception of breaks (12.00-13.00) and for specific user groups (Board of Directors and Marketing team).The implementation results show a drastic and measurable decrease in bandwidth usage. Social media traffic was reduced from 195 GB to 7 GB, equivalent to a 96.41% reduction.Meanwhile, streaming media traffic dropped from 448 GB to 52 GB, a reduction of 88.39%.The effectiveness of the policy was validated through analysis of firewall logs that consistently displayed a Deny status: UTM Blocked for thousands of prohibited access attempts. Based on this data, it is concluded that the Fortigate configuration is very effective in optimizing network bandwidth usage. This study recommends the use of schedule policies for flexibility and the integration of deep packet inspection to anticipate bypass methods by users.